2016
DOI: 10.3892/mmr.2016.4827
|View full text |Cite
|
Sign up to set email alerts
|

Nitidine chloride inhibits proliferation and induces apoptosis in colorectal cancer cells by suppressing the ERK signaling pathway

Abstract: Nitidine chloride (NC) is a natural bioactive phytochemical alkaloid that has displayed anticancer activity in various types of cancer. However, no evidence has been reported for the direct effect of NC on CRC cell proliferation and apoptosis, and the underling mechanisms to be fully elucidated. The present study aimed to investigate the influence of NC on the apoptosis and proliferation of CRC cells. The viability and proliferation of CRC cells was measured by MTT assay and a [3H] thymidine uptake assay. Apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…NC was identified to impede the proliferation of CRC cells and induce apoptosis [56]. NC treatment in CRC cells promoted the protein level of Bax, p53, cleaved caspase-3 and -9, and decreased Bcl-2 level and reduced the phosphorylation of ERK, which could lead to cell proliferation inhibition and apoptosis [56]. Elevation of STAT3 expression is observed and associated with metastasis in GC [57].…”
Section: Other Cancersmentioning
confidence: 99%
“…NC was identified to impede the proliferation of CRC cells and induce apoptosis [56]. NC treatment in CRC cells promoted the protein level of Bax, p53, cleaved caspase-3 and -9, and decreased Bcl-2 level and reduced the phosphorylation of ERK, which could lead to cell proliferation inhibition and apoptosis [56]. Elevation of STAT3 expression is observed and associated with metastasis in GC [57].…”
Section: Other Cancersmentioning
confidence: 99%
“…Many efforts have been devoted to study the CRC malignancy in terms of cell proliferation, apoptosis, migration and invasion. Zhai et al, found that nitidine chloride, a natural bioactive molecule, could induce apoptosis and inhibit proliferation in CRC cells via the signal‐regulated kinase (ERK) signalling pathway. The ERK‐dependent migration and invasion of CRC cells were demonstrated to be associated with matrix metalloproteinase 9 (MMP9) upregulation and epidermal growth factor receptor (EGFR) activation .…”
Section: Introductionmentioning
confidence: 99%
“…The activity of Akt is also regulated by casein kinase 2 (CK2) inhibitor (12). Mitogen-activated protein kinase (MAPK) signalling pathways relay and integrate signals from a wide range of stimuli and control cellular proliferation, cell cycle and apoptosis (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%